Adaptation Strategies of Multinational Corporations in Facing Regulatory Changes in the Global Business Environment: A Case Study in the Renewable Energy Sector - Dasep Supriatna (CV Putra Publisher, 2024)
Regulatory changes in global business, particularly in the renewable energy sector, require multinational companies (MNCs) to adopt rapid and effective adaptation strategies. This study aims to analyze how MNCs in the solar and wind energy sectors respond to increasingly complex and frequently changing cross-border regulatory dynamics. Using the Institutional Theory framework, specifically coercive, mimetic, and normative pressures, this research explores the institutional factors shaping corporate adaptation strategies. The research employs a multiple qualitative case study approach involving six MNCs operating in different jurisdictions. Data was collected through semi-structured interviews with senior managers, as well as analysis of company strategic documents and government regulations related to renewable energy. The results indicate that coercive pressures from governments and international institutions are the primary drivers of strategy change, while mimetic pressures emerge due to policy uncertainty, prompting companies to imitate competitors' practices. On the other hand, normative pressures from industry associations and stakeholder expectations reinforce the importance of social legitimacy and sustainability. The findings also indicate that adaptation is contextual and influenced by the specificity of national regulations and organizational capacity to manage change. This study contributes theoretically to understanding the strategic responses of MNCs through an institutional lens and provides practical implications for policymakers and industry actors in designing regulatory frameworks that promote an inclusive and adaptive global energy transition.